THE APPLICATION STUDY OF IMIDAZOLE DERIVATIVES IONIC LIQUID AS MEDIUM IN CELLULOSE HYDROLYSIS BY CELLULASE - YOGI SAPUTRA (NIM :10513021), MUHAMMAD
Cellulose is one of abundant renewable polymer and is widely present in plant biomass can be used as a source of sustainable energy. The crystalline structure of cellulose is form by the intermolecular and intramolecular hydrogen bonds causes cellulose more difficult to be hydrolyzed into sugars. Pre-treatments of cellulose to decrease the degree of crystallinity cellulose were performed by using ionic liquid, therefore this research shows imidazole derivatives ionic liquid that can be used as medium in cellulose hydrolysis. The ionic liquids were synthesized from the reaction between 1-methylimidazole with two of alkyl halides, 1-bromodecane and 1-bromododecane, utilizing Microwave Assisted Organic Synthesis (MAOS) method. The synthesis of ionic liquids were performed at 50 Ã‚Â°C for 60 minutes using microwave irradiation power of 300 watt to give 1-decyl-3-methylimidazolium bromide ([DMIM]Br) and 1-dodecyl-3-methylimidazolium bromide ([DDMIM]Br) with 58,03% and 32,91% yield, respectively. The ionic liquid products were characterized by FTIR and NMR spectroscopy. Based on the FTIR spectra analysis, both ionic liquids have typical peak of the C-H group vibration at 2900 cm-1. The results of the 1H NMR spectrum measurements (500 MHz, CDCl3) of the two ionic liquids shows proton signals of aromatic groups ( = 7,4 - 10,1 ppm) and proton signals of aliphatic groups ( = 1,1 - 4,2 ppm). Cellulose after dissolution in [DMIM]Br and [DDMIM]Br were subsequently characterized by FTIR spectroscopy and XRD analysis, which showed a decrease in the degree of crystallinity in cellulose from 91.32% to 89.64% and 83.85%, respectively. Reducing sugars assay by the DNS method indicated that both ionic liquids were capable to hydrolyze cellulose in the absence of cellulase enzymes (the range of reducing sugars concentration were 7 - 14 mM). Reducing sugars concentration after dissolution process of cellulose in each ionic liquid assisted with microwave irradiation and subsequently treated with enzymatic hydrolysis using cellulase were 55 - 75 mM of reducing sugars. Meanwhile, reducing sugars concentration produced from enzymatic hydrolysis of cellulose using cellulase in the ionic liquid medium assisted with microwave heating were 54 - 80 mM of reducing sugars. The results showed that the enzymatic hydrolysis of cellulose using cellulase performed more effectively in ionic liquids as medium assisted with microwave heating.